Naskah Manasik Haji Berbahasa Sunda dengan Pendekatan Tasawuf - E. Badri Yunardi (Jurnal Lektur Keagamaan, 2012)
The title of the manuscript, Manasik Hajj, is newly made, because the author does not mention it in the text. The title is made in accordance with the content of the text describing the guidance and instructions in performing the hajj pilgrimage. The manuscript is owned by Undang Darsa as a legacy from his ancestors. In the context of manuals for the hajj rituals, the manuscript Manasik Haji is unique because it provides Sufistic dimension on each phase of the pilgrimage. In general, however, the content of the manuscript has similarities with that of the fiqh books which explain the hajj rituals and are commonly used as manuals by the pilgrims.